Small Intestinal Bacterial Overgrowth in Subclinical Hypothyroidism of Pregnant Women - Wang, Biao; Xu, Yajuan; Hou, Xiaofeng; Li, Jingjing; Cai, Yanjun; Hao, Yingqi; Ouyang, Qian; Wu, Bo; Sun, Zongzong; Zhang, Miao; Ban, Yanjie (Frontiers in Endocrinology, 2021)
Objective: To evaluate the small intestinal bacterial overgrowth (SIBO) of subclinical hypothyroidism of pregnant women, and explore their possible relevance. Methods: In total, 224 pregnant women with subclinical hypothyroidism during pregnancy (study groupstudy group) and 196 pregnant women whose thyroid function was normal (control group) were enrolled in this study. Lactulose-based hydrogen and methane breath test was performed to evaluate the growth of intestinal bacteria. The serum-free thyroid hormone (FT4), thyroid-stimulating hormone (TSH), thyroid peroxidase antibody (TPOAb), body mass index (BMI) and gastrointestinal symptoms were detected and recorded. Results: The positive rates of SIBO were 56.7% and 31.6% in study group and control group, respectively. The levels of C response protein (CRP), abdominal distension and constipation in study group were higher than those in the control group. The risk of abdominal distension and constipation in SIBO-positive pregnant women were higher than that in SIBO-negative pregnant women, and the BMI of SIBO-positive patients in the two groups was lower than that of SIBO-negative patients in each group. In addition, the TPOAb-positive rate and TSH levels were higher but the FT4 level was lower in SIBO-positive patients compared to SIBO-negative patients in study group. Conclusion: The occurrence of subclinical hypothyroidism is related to SIBO, and the excessive growth of small intestinal bacteria may affect gastrointestinal symptoms.